Ranking the Psychological and Social Components of Life Purpose Formation in Adolescents - Muñoz, Nayelli; Hernández, Carlos (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and rank the key psychological and social components that contribute to the formation of life purpose among adolescents. Methods and Materials: This research employed a mixed-method exploratory–sequential design. The first phase consisted of a qualitative literature-based analysis conducted through thematic coding using NVivo 14 to identify major psychological and social components of adolescent life purpose formation. The review continued until theoretical saturation was reached, yielding nine central themes. In the second phase, a quantitative ranking survey was carried out with 250 adolescents aged 15–18 years from various high schools in Mexico, using a structured Likert-scale questionnaire derived from the qualitative findings. The collected data were analyzed using SPSS version 26, applying Friedman’s test to determine the mean rank order of each component and Cronbach’s alpha to confirm reliability. Findings: The analysis revealed statistically significant differences in the importance adolescents attributed to various life purpose components (χ² = 64.37, p < 0.001). Self-Identity Development received the highest mean rank (4.56), followed by Motivation and Goal Orientation (4.48) and Emotional Regulation (4.41). Cognitive Maturity (4.33) and Family Influence (4.25) also demonstrated strong relevance, while Peer and Social Relationships (4.17) and Educational Context and Mentorship (4.12) held moderate positions. Cultural and Societal Values (3.95) and Existential Awareness and Meaning-Making (3.82) were ranked lower, indicating that adolescents prioritize internal psychological mechanisms over external sociocultural influences in constructing their sense of purpose. Conclusion: The study concludes that life purpose formation in adolescents is primarily driven by internal psychological processes—especially identity, motivation, and emotional regulation—supported by social contexts such as family and education. Strengthening these components through targeted educational and counseling programs can enhance adolescents’ psychological well-being and long-term goal orientation.